The discursive construction of youth and government in Kenya’s 2024 Finance Bill digital protests - Omoke, Lillian Kemunto (Research Journal in Advanced Humanities, 2026)
Kenya’s 2024 Finance Bill protests marked a decisive shift in how political resistance is organized and expressed, with digitally mediated participation replacing traditional, centralized forms of mobilization. This study explores how youth-led social media discourse not only reflected but actively shaped the unfolding crisis. Discourse-Historical Approach and Connective Action Theory were used in the analysis of textual data from Twitter/X, Facebook, and TikTok collected during the months of May and June 2024 when there was heated online mobilization against the bill and the ultimate protest on 25 June, 2024. High-engagement posts were examined through qualitative discourse analysis. The analysis reveals a patterned use of language through which protesters constructed a sharp contrast between themselves and political elites. Political leadership was constructed as corrupt, detached, and failing; while citizens, particularly Gen Z, were positioned as corrective and morally grounded actors. This is achieved through a combination of nomination, predication, argumentation, and strategic modality. At the same time, slogans, metaphors, and lexical innovations generated a sense of collective identity. Intertextual references to historical, religious, and cultural narratives further anchor the protests within broader moral frameworks.